Quality Characteristics of Sourdough Bread with The Addition of Water Yest and Wheat-Mocaf Flours Combination - Intan Nurul Azni; Alberta Teresa Anggi Prabawati; Iman Basriman; Julfi Restu Amelia (Jurnal Teknik Pertanian Lampung (Journal of Agricultural Engineering), 2023)
Sourdough bread embraces health benefits due to the fermentation process carried out in the manufacturing process. The quality of sourdough bread is influenced by the specific microbes (yeast) that develop in the sourdough and the type of flour. The purpose of this study was to determine whether the type of fruit water yeast and the combination of wheat flour and mocaf could affect the quality of sourdough bread. The research design used was a factorial, completely randomized design with two factors and three replications. Water yeast from apple and salaca fruits as the first factors, and the second factor is a combination of wheat flour and mocaf as much as (100:0), (80:20), and (60:40). Physico-chemical and organoleptic characteristics were observed in the study. ANOVA and DMRT further tests were used for data analysis. Research shows the type of fruit water yeast can affect the moisture and carbohydrate content of sourdough bread. The combination of wheat flour and mocaf has a significant effect on the physical (hardness), chemical (content of water, ash, fat, protein, and carbohydrates), and organoleptic qualities (colour and the hedonic quality of texture) The combination of wheat flour and mocaf as much as 60:40 is a combination that produces sourdough bread of the highest quality. Keywords: Apple, Mocaf, Sourdough, Wheat flour, Zalacca